OPTIMASI LAMA WAKTU PEREBUSAN DENGAN PENAMBAHAN CUKA APEL TERHADAP KUALITAS FISIKOKIMIA DAN ORGANOLEPTIK KALDU TULANG KAMBING - Maharani, Nadia; Arinda, Nila; Ton, Sefri; Amaniyah, Maghfirotul; Khirzin, Muhammad Habbib (Universitas Muara Bungo, 2023)
This study aims to determine the effect of the length of boiling goat bone broth with the addition of apple vinegar based on physicochemical tests (viscosity, pH value and protein content) and organoleptic tests (color, taste, aroma and level of preference). This study used natural vinegar to avoid the use of synthetic vinegar acid and used apple vinegar to help the process of removing minerals and collagen found in goat bones. The research design used was a non-factorial Complete Random Design (RAL) and a non-factorial Group Random Design (RAK) including 4 treatments and 4 repeats, namely P1 = boiling time 6 hours, P2 = boiling time 12 hours, P3 = boiling time 18 hours and P4 = boiling time 24 hours. The results showed that the length of boiling time of goat bone broth had a real effect (P0.05) on viscosity with the highest value of 46.50 cP, pH value with the highest value of 5.42, and protein content with the highest value of 6.2% and organoleptic tests (color, aroma, taste and preference) of goat bone broth had a very real effect (P0.01). The best average result of the organoleptik test value of goat bone broth was at P4 (boiling time 24 hours).